IMPLEMENTASI PENDEKATAN SOSIOLOGI PADA PENDIDIKAN AGAMA ISLAM - Hamidah, Radhyatul (Universitas Muhammadiyah Makassar, 2022)
AbstractIslamic religious education as an ikhtiyariyah process that contains special characteristics and characteristics, namely the cultivation, development and consolidation of values that express themselves in the form of outer and inner behavior. Islamic religious education also trains one's sensitivity, so that in daily attitudes and behavior are dominated by deep feelings of Islamic ethical and spiritual values. With religious education, problems that arise in society can be addressed more wisely. In overcoming this can be done through a sociological approach. The purpose of this study was to obtain library information related to the implementation of a sociological approach to Islamic religious education. The results of this study explain the sociological approach to Islamic religious education and can be applied in everyday life in the community. Islamic religious education if applied with a different approach will also produce different things. Keywords: sociological approach, Islamic religious education